2014
DOI: 10.11648/j.ajim.20140205.12
|View full text |Cite
|
Sign up to set email alerts
|

Pain during Arterio-Venous Fistula (AVF) Cannulation

Abstract: Pain caused by medical care is a major concern of patients. Patients undergoing hemodialysis are submitted to two venous punctures at rate of two or three times per week and this by means of big needles gauge. Where pain during Arterio-Venous Fistula (AVF) cannulation should be the object of adequate take care. However few works are dedicated to it. Our purpose was to estimate prevalence, risk factors and take care of pain due to AVF cannulation to hemodialysis patients. It was monocenter study realized from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 10 publications
3
13
0
4
Order By: Relevance
“…These patients receive AVF cannulation three times per week and often express pain, which is their greatest concern during the insertion of a needle into AVF [2,3]. It has been reported that about 80% of patients undergoing hemodialysis experience moderate to very severe pain during AVF cannulation, but they do not receive pain relief [4]. Struggling with pain during hemodialysis can lead to frustration, despair, and lack of adherence to the therapeutic regimen [5].…”
Section: Introductionmentioning
confidence: 99%
“…These patients receive AVF cannulation three times per week and often express pain, which is their greatest concern during the insertion of a needle into AVF [2,3]. It has been reported that about 80% of patients undergoing hemodialysis experience moderate to very severe pain during AVF cannulation, but they do not receive pain relief [4]. Struggling with pain during hemodialysis can lead to frustration, despair, and lack of adherence to the therapeutic regimen [5].…”
Section: Introductionmentioning
confidence: 99%
“…Arteriovenous (AV) fistula is a type of surgery usually performed on the forearm that combines arteries and large veins to produce a fistula (Rosdahl & Kowalski, 2012). Patients receiv-ing hemodialysis often feel the effects of using AV fistulas, which includes pain during needle insertion (Kaza et al, 2014). Pain during AV fistula insertion is a real problem among hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pain during AV fistula insertion is the most common complaint among patients receiving hemodialysis (Figueiredo, Viegas, Monteiro, & Poly-De-Figueiredo, 2008). Patients undergoing AV fistula insertion for hemodialysis twice a week experience pain each time the procedure is carried out (Kaza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…6 Indeed, pain related to exposure to at least three punctures per week was reported as a major challenge by 57% of patients treated with hemodialysis. 7 Second, it may increase nonadherence to recommended dialysis regimen, 8 and thus increase mortality rate due to increase in cardiovascular and respiratory complications. 7 Second, it may increase nonadherence to recommended dialysis regimen, 8 and thus increase mortality rate due to increase in cardiovascular and respiratory complications.…”
Section: Introductionmentioning
confidence: 99%
“…5 Uncontrolled cannulation pain remains a major issue for two reasons: First, it imposes an additional burden to the quality of life. 7 Second, it may increase nonadherence to recommended dialysis regimen, 8 and thus increase mortality rate due to increase in cardiovascular and respiratory complications. 9 Nurses have been recognized as primary health-care providers for patients on hemodialysis.…”
Section: Introductionmentioning
confidence: 99%